Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1017/s1041610211000676
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate sexual behavior in a geriatric population

Abstract: This study suggests that ISB in the geriatric population is associated with a history of right frontal lobe stroke and with severity of dementia. Case examples of pharmacologic interventions are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 19 publications
(22 reference statements)
0
42
0
5
Order By: Relevance
“…11 Medroxyprogesterone has been shown to be helpful in geriatric populations in decreasing inappropriate sexual behaviors that included sexual comments, excessive hugging/ kissing, preoccupation with sex, masturbation in public, grabbing other's private parts, and exposing one's private part. 12 Medroxyprogesterone has also been shown to decrease desire for deviant behavior, frequency of masturbation, and deviant sexual behaviors in sex offenders. 13 The use of medroxyprogesterone in a patient with traumatic brain injury led to a decrease in excessive masturbation, touching private parts in public, and grabbing the private parts of others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Medroxyprogesterone has been shown to be helpful in geriatric populations in decreasing inappropriate sexual behaviors that included sexual comments, excessive hugging/ kissing, preoccupation with sex, masturbation in public, grabbing other's private parts, and exposing one's private part. 12 Medroxyprogesterone has also been shown to decrease desire for deviant behavior, frequency of masturbation, and deviant sexual behaviors in sex offenders. 13 The use of medroxyprogesterone in a patient with traumatic brain injury led to a decrease in excessive masturbation, touching private parts in public, and grabbing the private parts of others.…”
Section: Discussionmentioning
confidence: 99%
“…17 Other medication classes that have been used to treat hypersexual behaviors are selective serotonin reuptake inhibitors 18 and atypical antipsychotics, such as risperidone (0.5-2 mg) and olanzapine, even though concerns have been raised for these medications regarding significant metabolic and extrapyramidal side effects. 12 Case studies in an elderly population showed benefits with donepezil 19 and carbamazepine. 20 There are limited numbers of studies in children and adolescents with autism who exhibit hypersexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Dimensions of ER other than impulse control may play an important role in hypersexuality at this qualitative level. For example, an inability to use situationally appropriate ER strategies might account for the increased incidence of inappropriate sexual behavior during transitions between different stages of life, such as the transition to adulthood (Castellano, Velotti, Crowell, & Zavattini, 2013;Velotti et al, 2015) or old age (Bardell, Lau, & Fedoroff, 2011).…”
Section: Hypersexuality Through the Lens Of Emotion Regulationmentioning
confidence: 99%
“…Other authors (Bardell, et al, 2011) have reported that there is an increased risk of one component of HD, inappropriate sexual behavior À where sexual behavior is defined as inappropriate if it interferes with normal living or is pursued at inconvenient times or with unwilling partners (Higgins, Barker, & Begley, 2004) À in geriatric populations. We assume that sexual behavior in the elderly is generally considered inappropriate on grounds of the quality rather than quantity of sexual behaviors.…”
Section: Hypersexuality Through the Lens Of Emotion Regulationmentioning
confidence: 99%
“…Examining physical status and current medications is needed to determine (bio)medical causes. Different classes of medications have shown to induce uncontrolled sexual behaviour, in clinical settings [22]. For example, atypical antipsychotics can induce uncontrolled sexual behaviour by blocking the effects of selective serotonin reuptake inhibitors [23].…”
Section: Assessmentmentioning
confidence: 99%